ЛИЧНОСТНЫЕ ХАРАКТЕРИСТИКИ И УРОВЕНЬ ТРЕВОГИ У ПОДРОСТКОВ С ИЗБЫТОЧНОЙ МАССОЙ ТЕЛА И ОЖИРЕНИЕМ - Гурова, Маргарита Михайловна; Комиссарова, Марина Юрьевна; Евдокимова, Нина Викторовна; Мильнер, Евгения Борисовна (FORCIPE, 2022)